Oncogenic Mutations and Tumor Microenvironment Alterations of Older Patients With Diffuse Large B-Cell Lymphoma - Zhu, Yue; Fu, Di; Shi, Qing; Shi, Ziyang; Dong, Lei; Yi, Hongmei; Liu, Zhenhua; Feng, Yan; Liu, Qian; Fang, Hai; Cheng, Shu; Wang, Li; et al. (Frontiers in Immunology, 2022)
The incidence of diffuse large B cell lymphoma (DLBCL) increases by age and older DLBCL are commonly related to poor prognosis. However, the clinical and biological features of older DLBCL patients remain to be determined. A total of 2445 patients with newly diagnosed DLBCL were enrolled for clinical data analysis according to age at diagnosis, with tumor samples of 1150 patients assessed by DNA sequencing and 385 patients by RNA sequencing. Older DLBCL presented advanced disease stage, elevated serum lactate dehydrogenase, poor performance status, multiple extranodal involvement, high percentage of double expressor subtype, and adverse clinical outcome. According to molecular features, the mutation frequencies of PIM1, MYD88, BTG2, CD79B, TET2, BTG1, CREBBP, and TBL1XR1 showed significantly increasing trend with age. These mutations were involved in B cell receptor/NF-B signaling, B-cell differentiation, and histone acetylation based on biological functions. Older DLBCL also manifested reduction in CD4+ naïve T and CD8+ naïve T cells, as well as increased recruitment of exhausted T cells and macrophages, leading to immunosuppressive tumor microenvironment. Our work thus contributes to the understanding of aging-related oncogenic mutations and tumor microenvironment alterations in lymphoma progression, and may provide new insights to mechanism-based targeted therapy in DLBCL.